Perencanaan Rabat Beton Jalan Lingkungan pada Gang Sei Pelanjo Desa Negeri Baru Kabupaten Ketapang - Putrini, Saima; Marwan, Dani; Rustam Efendi, Uti (Teknik Sipil, Politeknik Negeri Ketapangg, 2022)
The road section on Gang Sei Pelanjo, Desa Negeri Baru, Kabupaten Ketapang is categorized as a road whose condition is still sandy and narrow due to the many small trees growing on the side of the road, so the road tends to be difficult to pass. The purpose of this study was to determine the CBR value of the original soil at the research location based on field CBR testing to obtain the value of the soil bearing capacity on the road, to obtain the results of planning a rigid pavement structure that suits the needs both in terms of safety, and the strength of the road segment using SNI 8457-2017 method. The research method was carried out by measuring the length of the road, the width of the road, the road shoulder to determine the condition of the existing road, then a traffic survey (LHR) to determine the volume and type of vehicles and a field CBR survey using the DCP tool to evaluate the strength of the subgrade and road foundation. The results of the analysis and calculation of the thickness of the rigid pavement structure for the road section on Gang Sei Pelanjo, Desa Negeri Baru,Kabupaten Ketapang, obtained the concrete used for the superstructure with a thickness of 0.15 m adjusted to the pavement thickness planning calculation. The under foundation of thin concrete uses a thickness of 0.5 m and uses a sub-base layer with a thickness of 0.15 m. The Budget Plan for the Gang Sei Pelanjo road, Desa Negeri Baru,Kabupaten Ketapangwith a road length of 200 m and a road width of 3 m is Rp. 186,512,082.89